The Influence of Psychological Capital on Burnout and Work Engagement through Job Resources in PT. XYZ - Stanley Aldrich Wijono; Patrick Giovanni Wongsosaputro (iBuss Management, 2019)
Psychological well-being is very essential in sustaining good employee performance. Many scholars have found that psychological capital (PsyCap) influence psychological well-being (burnout and work engagement). Some had argued that the role of job resources (external factors) mediates the relationship between them. Therefore, the purpose of this research is to investigate the influence of PsyCap on burnout and work engagement through satisfaction with the job resources.The data were randomly collected from 200 employees in Indonesia’s second biggest towel and tissue manufacturing company. A questionnaire was used, which consists of PCQ-24, job resources measurement (Parker & Hyett, 2011), the Maslach Burnout Inventory, and the Utrecht Work Engagement Scales. Then, the data were analyzed using Structural Equation Modeling. It is found that the impact of (1) PsyCap on satisfaction with job resources was positive, (2) satisfaction with job resources on burnout was negative, (3) satisfaction with job resources on work engagement was positive, and (4) satisfaction with job resources was partially mediating the relationships. All of the results are statistically significant. Keywords: Psychological Capital, Job Resources, Burnout, Work Engagement.